Untreated Isolated Torsion of the Epididymis in an Adolescent - Birkan, Zulfu; Kalayci, Tugce Ozlem; Karakeci, Ahmet; Sonmezgoz, Fitnet; Albayrak, Eda; Bozdag, Pinar Gundogan (Elsevier Science Inc, 2016)
Although torsion of epididymis is extremely rare, it should be kept in mind in the differential diagnosis of acute scrotal pain in adolescents. We report here a very rare cause of acute scrotum: torsion of the epididymis. (C) 2016 The Authors. Published by Elsevier Inc. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Color Doppler ultrasonography; Scrotum; Ischemia; Necrosis